2020
DOI: 10.1088/1748-9326/ab9d00
|View full text |Cite
|
Sign up to set email alerts
|

A systematic map of responses to climate impacts in urban Africa

Abstract: Over time African cities and their residents have responded to climate impacts in increasingly creative ways, based on local knowledge and available resources. Overviews of adaptation policy, plans and actions have largely been lacking for Africa, particularly at the local, city level. We applied a systematic map to assess what the human responses to climate impacts are in African cities, noting the climate drivers of these actions, the range of responses, where they have taken place, and who the actors are. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…A recent synthesis 53 found that a majority of these assessments focus on developed regions, particularly North America and Europe, 13,15,18,23,54 although some recent analyses include progress data from the Global South. 14,16,17,19,22 Furthermore, diverse methodological approaches are used to systematize information. Yet, most assessments focus exclusively on standalone physical ''plans'' rather than on other policy outputs.…”
Section: The Urban Adaptation Action Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent synthesis 53 found that a majority of these assessments focus on developed regions, particularly North America and Europe, 13,15,18,23,54 although some recent analyses include progress data from the Global South. 14,16,17,19,22 Furthermore, diverse methodological approaches are used to systematize information. Yet, most assessments focus exclusively on standalone physical ''plans'' rather than on other policy outputs.…”
Section: The Urban Adaptation Action Gapmentioning
confidence: 99%
“…A large number of initiatives have emerged over the past decade; hundreds (and possibly thousands) of cities and localities across the world are preparing for climate change through plans, pol-icies, privately supported projects, and community-based actions. [13][14][15][16][17][18][19][20][21][22][23] Many of these efforts focus on assessing local risks and building internal local capacity, leadership, and resources to plan for future risks. 24 Although efforts over the past decade have increased awareness of climate change in cities and localities worldwide, recent scientific assessments of these efforts paint a very mixed picture about the extent to which adaptation outcomes have been broadly effective, equitable (especially across divides in wealth, education, ethnicity, religion, age, gender, abilities, values, or worldviews), and legitimate across different social and geographical contexts.…”
Section: Introductionmentioning
confidence: 99%
“…They can mitigate the impact of flooding by organising the clean-up of drains, they can protect their houses from storms by reinforcing their roofs, and they can keep or establish networks with social relations in rural areas to allow the transit of food. Nevertheless, private initiatives which constitute the majority of action to prevent short-term climate variability cannot compensate for a complete lack of planning in response to long-term climate change (Hunter et al 2020, Mashi et al 2020. On the other hand, municipalities have limited capacity for intervention.…”
Section: Conclusion: Inclusiveness or Disintegration?mentioning
confidence: 99%
“…Recent assessments of urban climate adaptation have evaluated the contents, quality, means and scope of adaptation (e.g. Aguiar et al 2018;Araos et al 2016;Carmin et al 2012;Guyadeen et al 2019;Hunter et al 2020;Le 2020;Lesnikowski et al 2019;Olazabal et al 2019b;Olazabal & Ruiz De Gopegui 2021;Reckien et al 2018;Shi et al 2015;Woodruff & Stults 2016). This body of literature offers an incomplete analysis of how urban adaptation is institutionalised (Patterson 2021).…”
Section: Introductionmentioning
confidence: 99%
“…With a few exceptions (e.g. Hunter et al 2020), assessments focus on identifying and evaluating adaptation policies and plans Patterson 2021). Studies of the dimensions and diversity of adaptation institutions and their formation (Patterson 2018(Patterson , 2021 have not yet engaged explicitly with integrating adaptation institutions into existing governance processes.…”
Section: Introductionmentioning
confidence: 99%